Managing vitamin D supplementation in elite academy footballers - Verma, A.; Maynard, T.; Moxon, J. (British Journal of Sports Medicine, 2021)
Background The maintenance of phosphate and calcium homeostasis alongside optimal vitamin D status is essential for bone health. Moreover, low vitamin D is associated with an increased risk of stress fracture, impaired muscular remodelling and increased risk of upper respiratory tract infections.